Constructing audience quantification: Social influences and the development of norms about audience analytics and metrics - Zamith, Rodrigo; Belair-Gagnon, Valerie; Lewis, Seth C (New media & society, 2020)
Audience analytics and metrics are ubiquitous in today’s media environment. However, little is known about how creative media workers come to understand the social norms related to those technologies. Drawing on social influence theory, this study examines formal and informal socialization mechanisms in U.S. newsrooms. It finds that editorial newsworkers express receiving a moderate amount of training on the use of analytics and metrics, which is typically provided by their organization; primarily look to people within the organization, and especially superiors, to understand the social norms; learn about those norms mostly through observation and communication about others’ experiences with the technology rather than their own; and that experiences are influenced by the organizational context and the individual’s position in the editorial hierarchy. This leads to a broader intervention to our understanding of the social structures and individual dispositions that influence how emerging technologies are experienced across organizational and institutional environments.